Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

Modified sodium iron phosphate pyrophosphate cathode material was prepared by co-precipitation and manganese ion regulation of particle nucleation and growth rate. This method solves the problems of low density and voltage of existing materials, and achieves high energy density and improved stability, making it suitable for sodium-ion batteries.

CN120834200APending Publication Date: 2025-10-24BEI JING XI BEI DONG LI KE JI YOU XIAN GONG SI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510993903.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing sodium iron phosphate pyrophosphate materials suffer from problems such as low compaction density, low operating voltage, and low discharge specific energy, making it difficult to meet the high energy density and stability requirements of sodium-ion batteries.

Method used

Modified sodium iron phosphate pyrophosphate cathode material was prepared by co-precipitation method. The nucleation and growth rate of particles were regulated by manganese ions, making the particles more compact. The conductivity and structural stability were improved by manganese doping, resulting in a material with high discharge plateau voltage and energy density.

Benefits of technology

It significantly improves the compaction density and conductivity of the material, enhances the discharge plateau voltage and energy density, and exhibits excellent rate performance and cycle performance, meeting the high energy density and stability requirements of sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120834200A_ABST
    Figure CN120834200A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a modified ferric sodium pyrophosphate positive electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) reacting an oxalic acid source, an iron source and a manganese source in an aqueous solution to obtain an iron manganese oxalate intermediate; and (2) uniformly mixing the ferric manganese oxalate intermediate with sodium phosphate, sodium pyrophosphate and a reducing agent, heating to obtain a gelatinous solid, drying and sintering to obtain the modified ferric sodium phosphate pyrophosphate positive electrode material. The nucleation and growth rate of particles in the precipitation process is regulated and controlled through manganese ions by adopting a coprecipitation method, so that the particles are more tightly stacked, the compaction density of the product is effectively improved, meanwhile, the conductivity and the structural stability of the ferric sodium pyrophosphate can be effectively improved through manganese doping, and the performance of the ferric sodium pyrophosphate is improved. Therefore, the prepared modified sodium ferric pyrophosphate positive electrode material has relatively high discharge platform voltage and energy density, and excellent rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified sodium iron pyrophosphate cathode material, a preparation method thereof, and applications thereof. Background Art

[0002] Compared with traditional lithium-ion batteries, sodium has inherent advantages such as low resource cost, wide distribution and abundant reserves. Therefore, sodium-ion batteries are expected to become the main force in the intermittent renewable energy market, and the development of electrode materials is one of the most important goals of improving sodium-ion batteries.

[0003] Among the positive electrode materials for sodium ion batteries, sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7) has the advantages of low raw material price, stable structure, high theoretical capacity (~129mAh / g), high working voltage (~3.1V, Na + The advantages of sodium ion battery cathode material include low density, low operating voltage and low discharge specific energy.

[0004] Therefore, it is hoped to provide a new modified sodium iron pyrophosphate cathode material and a preparation method thereof. Summary of the Invention

[0005] In order to solve the above technical problems, the present invention provides a modified sodium ferric pyrophosphate positive electrode material, a preparation method and application thereof. The present invention uses a co-precipitation method to prepare the modified sodium ferric pyrophosphate positive electrode material, and regulates the nucleation and growth rates of particles during the precipitation process by manganese ions, so that the stacking between the particles is tighter, thereby effectively improving the compaction density of the product. At the same time, manganese doping can effectively improve the conductivity and structural stability of sodium ferric pyrophosphate, so that the prepared modified sodium ferric pyrophosphate positive electrode material has a higher discharge platform voltage and energy density, and thus has excellent rate performance and cycle performance.

[0006] In a first aspect, the present invention provides a method for preparing a modified sodium iron pyrophosphate positive electrode material, the preparation method comprising the following steps:

[0007] (1) reacting an oxalic acid source with an iron source and a manganese source in an aqueous solution to obtain an iron-manganese oxalate intermediate;

[0008] (2) The ferromanganese oxalate intermediate is mixed with sodium phosphate, sodium pyrophosphate and a reducing agent, and then heated to obtain a gel-like solid, which is then dried and sintered to obtain the modified sodium ferric pyrophosphate positive electrode material.

[0009] The application utilizes the coprecipitation method to prepare the modified sodium iron pyrophosphate positive electrode material, controls the nucleation and growth rate of the particles in the precipitation process through manganese ions, makes the accumulation between the particles more compact, thereby effectively improves the compaction density of the product, and the manganese doping can effectively improve the conductivity and structural stability of the sodium iron pyrophosphate, so that the prepared modified sodium iron pyrophosphate positive electrode material has higher discharge platform voltage and energy density, in particular:

[0010] The application first prepares the iron manganese oxalate intermediate, and then utilizes the coprecipitation method to prepare the modified sodium iron pyrophosphate positive electrode material, the introduction of Mn 2+ can change the growth habit and surface properties of the precipitated particles, control the nucleation and growth rate of the particles in the precipitation process, make the particle size distribution of the generated particles more uniform, and the accumulation between the particles more compact. The optimization of this microstructure improves the compaction performance of the material in the electrode preparation process, increases the mass of active substances in the unit volume, thereby improving the compaction density of the electrode material. Higher compaction density means that more active substances can be loaded in the same volume of battery, further improving the volume energy density of the battery, meeting the requirements of small size and high energy density of the battery in actual application. At the same time, the manganese doping makes the modified sodium iron pyrophosphate positive electrode material prepared by the application have excellent electrochemical performance:

[0011] ①Improve the platform voltage. Mn 2+ / Mn 3+ The redox potential (about 3.6-3.8V vs. Na + / Na) is higher than the potential of Fe 2+ / Fe 3+ (approximately 3.0-3.2V vs. Na+ / Na), this difference is due to the stronger interaction between the 3d orbital electrons of Mn and the ligand orbitals, resulting in higher crystal field stabilization energy. When Mn partially replaces Fe, the material will exhibit a double voltage platform feature, and the appearance of the Mn-related platform can significantly improve the average working voltage. It is worth noting that due to the introduction of Mn, the lattice parameter may change (especially the adjustment of Fe / Mn-O bond length and bond angle), and the Jahn-Teller effect in Mn 3+ (d 4 configuration) may cause local lattice distortion, but this distortion will be inhibited in the rigid framework structure of NFPP, so the effect of voltage platform improvement is more significant than in layered materials. In addition, Mn doping may also indirectly affect the redox potential of Fe 2+ / Fe 3+ through changing the local coordination environment of Fe, and this synergistic effect makes the voltage curve may exhibit a non-simple superposition feature.

[0012] ② Improve energy density. Energy density is determined by voltage platform and specific capacity. 2+ The ionic radius is approximately Fe 2+ The ionic radius is approximately Although the difference in ionic radius between the two will cause a slight expansion of the lattice, the open framework structure of NFPP can better accommodate this change. First-principles calculations show that the hybridization of the 3d orbital of Mn and the 2p orbital of [PO4] tetrahedron may form a wider conduction band, which is conducive to electron conduction and thus improves the utilization rate of active materials. More importantly, Mn 2+ / Mn 3+ The redox reaction provides additional electron transfer pathways for the material, theoretically increasing the theoretical capacity from approximately 128 mAh / g to approximately 140 mAh / g. In practical applications, Mn doping may also inhibit Fe dissolution, reducing active material loss during cycling and enabling the high energy density characteristics to be maintained more sustainably.

[0013] ③ Improve the cycle stability. NFPP itself has excellent cycle stability due to its three-dimensional framework structure, and the introduction of Mn further strengthens this feature. From the perspective of crystal chemistry, the Mn-O bond (approx. ) than Fe-O bond (approx. ) is slightly longer but has stronger bond energy (Mn-O bond energy is about 402kJ / mol, Fe-O bond energy is about 390kJ / mol). This stronger bonding can effectively inhibit the excessive expansion and contraction of the lattice during charge and discharge, alleviating the Na + In addition, Mn 3+ Although the Jahn-Teller effect may theoretically cause structural instability, in actual doping systems, due to the limited Mn content and the rigid [PO4] framework, its negative impact will be significantly weakened. More importantly, Mn doping can inhibit the Fe 2+ The disproportionation reaction (2Fe 2+ →Fe 3+ +Fe), reducing Fe dissolution. At the same time, Mn doping can also form a more uniform electron cloud distribution, thereby reducing charge transfer resistance.

[0014] As a preferred technical solution of the present invention, step (1) is: continuously adding an oxalic acid source to the aqueous solution of the iron source and the manganese source for reaction, so as to better control the reaction process, control the size of the spherical particles in the early stage of product formation, thereby reducing the particle size of the final product and increasing the compaction density.

[0015] As a preferred technical solution of the present application, the reaction in step (1) is carried out under the protection of an inert gas atmosphere, the inert gas being selected from any one or more of nitrogen, argon or helium, to prevent Fe 2+ from being oxidized to Fe 3+ .

[0016] The present application first prepares an iron-manganese oxalate intermediate (Fe y Mn z (C2O4) y+z , 2.9≤y+z≤3, 0.1<z≤1.5), wherein the solubility product K sp ≈10 -7.4 of FeC2O4 can form a precipitate when the pH is greater than 1.5, but Fe 2 + is easily oxidized to Fe 3+ and generates more difficultly soluble Fe2(C2O4)3(K sp ≈10 -20 ), Fe 2+ and Fe 3+ are easily hydrolyzed to generate Fe(OH)2(K sp ≈10 -15 ) and Fe(OH)3(K sp ≈10 -38 ), so that the target product FeC2O4 can be obtained within the pH range of 1.5-4.0. The solubility product K sp ≈10 -5.2 of MnC2O4 can form a precipitate when the pH is greater than 3.0, but Mn 2+ is easily hydrolyzed to generate Mn(OH)2(K sp ≈10 -12.8 ), so that the target product MnC2O4 can be obtained within the pH range of 3.0-6.5.

[0017] Therefore, when the pH is within the range of 3.0-4.0, both metal ions can be precipitated as oxalate, thereby obtaining the iron-manganese oxalate intermediate.

[0018] As a preferred technical solution of the present application, the pH in step (1) is 3.3-3.7, such as 3.3, 3.4, 3.5, 3.6, 3.7, etc.

[0019] As a preferred technical solution of the present application, the pH is adjusted by a pH adjusting agent, the pH adjusting agent being selected from any one or more of sulfuric acid (H2SO4), nitric acid (HNO3) and hydrochloric acid (HCl).

[0020] As a preferred technical solution of the present application, the pH regulator is selected from the acid corresponding to the anion in the iron source, for example, when the iron source is ferric sulfate, the pH regulator is sulfuric acid; when the iron source is ferric nitrate, the pH regulator is nitric acid, so as to minimize the types of impurities in the solution, facilitating subsequent water washing to remove impurities.

[0021] As a preferred technical solution of the present application, the molar ratio of iron elements in the iron source to manganese elements in the manganese source is (1.4-2.9):(0.1-1.5), for example, 1.4:0.1, 1.4:0.5, 1.4:1, 1:1, 2:0.1, 2:1, 2:1.5, 2.9:0.1, 2.9:0.5, 2.9:1, 2.9:1.5, etc.

[0022] As a preferred technical solution of the present application, the ratio of the total molar amount of iron elements in the iron source to manganese elements in the manganese source to the molar amount of oxalate ions in the oxalate source is 1:(1-1.1), for example, 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, etc.

[0023] As a preferred technical solution of the present application, the oxalate source is selected from any one or more of oxalic acid (H2C2O4), ammonium oxalate ((NH4)2C2O4), and sodium oxalate (Na2C2O4).

[0024] As a preferred technical solution of the present application, the iron source is selected from any one or more of ferrous sulfate (FeSO4), ferrous nitrate (Fe(NO3)2), and ferrous chloride (FeCl2).

[0025] As a preferred technical solution of the present application, the manganese source is selected from any one or more of manganese sulfate (MnSO4), manganese nitrate (Mn(NO3)2), and manganese chloride (MnCl2), preferably the anion of the manganese source is the same as the anion of the iron source, for example, when the iron source is ferric sulfate, the manganese source is manganese sulfate; when the iron source is ferrous chloride, the manganese source is manganese chloride, so as to minimize the types of impurities in the solution, facilitating subsequent water washing to remove impurities.

[0026] As a preferred technical solution of the present application, the molar ratio of the ferric manganese oxalate intermediate to the sodium phosphate salt of sodium, the sodium pyrophosphate salt of sodium, and the reducing agent is 1:2:1:(1.5-6), so as to ensure obtaining the target product.

[0027] As a preferred technical solution of the present application, the sodium phosphate salt of sodium is selected from any one or more of trisodium phosphate (Na3PO4), disodium hydrogen phosphate (Na2HPO4), monosodium phosphate (NaH2PO4), and sodium ammonium hydrogen phosphate (NaNH4HPO4).

[0028] As a preferred technical solution of the present application, the sodium pyrophosphate is selected from sodium pyrophosphate (Na4P2O7) and / or sodium dihydrogen pyrophosphate (Na2H2P2O7).

[0029] As a preferred technical solution of the present application, the reducing agent is selected from any one or more of citric acid (C6H8O7), oxalic acid (C2H2O4), sucrose (C 12 H 22 O 11 ) and ascorbic acid (C6H8O6).

[0030] As a preferred technical solution of the present application, the temperature of the heating is 50-80℃, such as 50℃, 60℃, 70℃, 80℃, etc.

[0031] As a preferred technical solution of the present application, the temperature of the drying is 110-125℃, such as 110℃, 115℃, 120℃, 125℃, etc., preferably 120℃; the time of the drying is 18-36h, such as 18h, 24h, 30h, 36h, etc., preferably 24h.

[0032] As a preferred technical solution of the present application, the sintering is carried out under the protection of an inert gas atmosphere, the inert gas being selected from any one or more of nitrogen, argon or helium.

[0033] As a preferred technical solution of the present application, the method of the sintering is calcination at 350℃ for 3-8h, followed by calcination at 550-650℃ for 8-18h, the heating rate being 2-5℃ / min, preferably 2℃ / min. Among them, the 3-8h can be 3h, 4h, 5h, 6h, 7h, 8h, etc., the 550-650℃ can be 550℃, 580℃, 600℃, 620℃, 650℃, etc., the 8-18h can be 8h, 10h, 12h, 14h, 16h, 18h, etc., and the 2-5℃ / min can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, etc.

[0034] In a second aspect, the present application provides a modified sodium iron pyrophosphate positive electrode material prepared by the preparation method of the first aspect.

[0035] As a preferred technical solution of the present application, the modified sodium iron pyrophosphate positive electrode material is Na x Fe y Mn z (PO4)2P2O7, wherein 4≤x≤4.18, 2.9≤y+z≤3, 0.1<z≤1.5, and x+2y+2z=10.

[0036] Wherein, x can be 4, 4.05, 4.1, 4.15, 4.18, etc., z can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.5, etc., and y+z can be 2.9, 2.92, 2.94, 2.96, 2.98, 3, etc.

[0037] In a third aspect, the present application provides a positive electrode sheet, which comprises the modified sodium pyrophosphate ferric phosphate positive electrode material of the second aspect.

[0038] In a fourth aspect, the present application provides a sodium ion battery, which comprises the positive electrode sheet of the third aspect.

[0039] Compared with the prior art, the technical scheme provided by the embodiments of the present application has the following advantages:

[0040] The present application uses a coprecipitation method to prepare a modified sodium pyrophosphate ferric phosphate positive electrode material. By adjusting the nucleation and growth rate of particles in the precipitation process through manganese ions, the particles are more closely packed, thereby effectively improving the compaction density of the product. Meanwhile, manganese doping can effectively improve the conductivity and structural stability of sodium pyrophosphate ferric phosphate, so that the prepared modified sodium pyrophosphate ferric phosphate positive electrode material has a higher discharge platform voltage and energy density, and thus has excellent rate performance and cycle performance. BRIEF DESCRIPTION OF DRAWINGS

[0041] The accompanying drawings, which are incorporated into and form part of the specification, illustrate embodiments consistent with the present application and, together with the specification, serve to explain the principles of the application.

[0042] In order to more clearly illustrate the technical schemes in the embodiments of the present application or the prior art, the accompanying drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, for those skilled in the art, other drawings can also be obtained without creative labor based on these drawings.

[0043] Figure 1 XRD pattern of the modified sodium pyrophosphate ferric phosphate positive electrode material prepared for Example 1;

[0044] Figure 2 First cycle charge-discharge curve of the button cell assembled by the positive electrode material prepared for Examples 1-3 and Comparative Example 1 at 0.1C;

[0045] Figure 3 Rate performance diagram of the button cell assembled by the positive electrode material prepared for Examples 1-3 and Comparative Example 1;

[0046] Figure 4The long cycle performance chart of the assembled button cell of the positive electrode material prepared for Examples 1-3 and Comparative Example 1 at 1C is shown in the following figure. DETAILED DESCRIPTION

[0047] In order to enable a more complete understanding of the above-mentioned objects, features and advantages of the present application, the schemes of the present application will be further described below. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0048] In the following description, a large number of specific details are set forth in order to facilitate a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein; obviously, the embodiments in the description are only a part of the embodiments of the present application, rather than all the embodiments.

[0049] Example 1

[0050] The present embodiment provides a modified pyrophosphate sodium iron phosphate positive electrode material and a preparation method thereof, the modified pyrophosphate sodium iron phosphate positive electrode material is Na4Fe 1.5 Mn 1.5 (PO4)2P2O7, and the preparation method comprises the following steps:

[0051] (1) according to the molar ratio of ferrous ion, manganese ion and oxalate ion is 1:1:2.05, and ferrous sulfate, manganese sulfate and ammonium oxalate are calculated and weighed, ammonium oxalate is added into deionized water to prepare solution A with a C2O4 2- concentration of 0.19 mol / L, and ferrous sulfate and manganese sulfate are added into deionized water to prepare solution B with a concentration of 0.19 mol / L of the sum of Fe 2+ and Mn 2+ , and sulfuric acid is added to adjust the pH to 3.5.

[0052] (2) solution B is added into a reaction kettle, nitrogen gas is continuously introduced as a protective gas, solution A is introduced at a flow rate of 1 L / h, after complete reaction, the precipitate is centrifuged and dried to obtain an oxalic acid iron manganese intermediate Fe 1.5 Mn 1.5 (C2O4)3.

[0053] (3) according to the molar ratio of oxalic acid iron manganese intermediate: sodium dihydrogen phosphate: disodium pyrophosphate: citric acid is 1:2:1:4, the corresponding raw materials are weighed and added into deionized water, and stirred into a gel at 60℃, and dried in an oven at 125℃ for 18h to obtain an amorphous powder. The above powder is loaded into a sagger, and sintered in a box furnace under argon protection, the heating rate is 2℃ / min, the first stage is 350℃ for 3h, and the second stage is 580℃ for 10h; after grinding, the powder is sieved through a 300 mesh sieve to obtain the modified pyrophosphate sodium iron phosphate positive electrode material.

[0054] Example 2

[0055] The present example provides a modified sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the modified sodium iron phosphate pyrophosphate positive electrode material is Na 4.18 Fe 2.31 Mn 0.6 (PO4)2P2O7, the preparation method comprises the following steps:

[0056] (1) according to the molar ratio of ferrous ion, manganese ion, oxalate ion is 1.54:0.4:2.1 and is calculated and weighed ferrous chloride, manganese chloride and sodium oxalate, sodium oxalate is added to deionized water to prepare C2O4 2- Concentration is 0.20mol / L solution A, ferrous chloride and manganese chloride are added to deionized water to prepare solution B, and the concentration of Fe 2+ And Mn 2+ The sum is 0.194mol / L and hydrochloric acid is added to adjust the pH to 3.4.

[0057] (2) solution B is added to the reaction kettle, argon gas is continuously introduced as protective gas, solution A is introduced at a flow rate of 1L / h, after complete reaction, the precipitate is centrifuged and dried to obtain the oxalate iron manganese intermediate Fe 2.31 Mn 0.6 (C2O4) 2.91 .

[0058] (3) according to the molar ratio of oxalate iron manganese intermediate: disodium hydrogen phosphate: sodium pyrophosphate: ascorbic acid is 1:2:1:2, the corresponding raw materials are weighed and added to deionized water, stirred into gel at 50℃, dried in an oven at 120℃ for 24h to obtain amorphous powder. The above powder is loaded into a crucible, sintered in a box furnace under argon protection, the heating rate is 2℃ / min, the first stage is 350℃ for 5h, the second stage is 550℃ for 12h; after grinding, pass through a 300 mesh sieve to obtain the modified sodium iron phosphate pyrophosphate positive electrode material.

[0059] Example 3

[0060] The present example provides a modified sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the modified sodium iron phosphate pyrophosphate positive electrode material is Na 4.12 Fe 1.74 Mn 1.2 (PO4)2P2O7, the preparation method comprises the following steps:

[0061] (1) according to the molar ratio of ferrous ion, manganese ion, oxalate ion is 1.54:0.4:2.1 and is calculated and weighed ferrous chloride, manganese chloride and sodium oxalate, sodium oxalate is added to deionized water to prepare C2O4 2-Solution A with a concentration of 0.22 mol / L, ferrous nitrate and manganese nitrate were added to deionized water to prepare Fe 2+ and Mn 2+ Solution B with a concentration of 0.196 mol / L of the sum of the concentrations of Fe

[0062] (2) Solution B was added to the reaction kettle, and argon gas was continuously introduced as a protective gas. Solution A was continuously introduced into the reaction kettle at a flow rate of 1 L / h. After complete reaction, the precipitate was centrifuged and dried to obtain the iron manganese oxalate intermediate Fe 1.74 Mn 1.2 (C2O4) 2.94 .

[0063] (3) The corresponding raw materials were weighed according to the ratio of iron manganese oxalate intermediate: trisodium phosphate: disodium hydrogen pyrophosphate: sucrose = 1:2:1:4, and deionized water was added. The mixture was stirred to form a gel at 70°C, and then dried in an oven at 125°C for 32 h to obtain an amorphous powder. The powder was loaded into a crucible and sintered in a box furnace under argon protection. The heating rate was 2°C / min, the first stage was 350°C for 6 h, and the second stage was 610°C for 10 h. After grinding, the powder was sieved through a 300 mesh sieve to obtain the modified pyrophosphate sodium iron phosphate positive electrode material.

[0064] Comparative Example 1

[0065] This comparative example provides a pyrophosphate sodium iron phosphate positive electrode material and a preparation method thereof. The pyrophosphate sodium iron phosphate positive electrode material is Na4Fe3(PO4)2P2O7, and the preparation method comprises the following steps:

[0066] (1) The molar ratio of Fe 3+ : PO4 3- : P2O7 4- was calculated and the corresponding amounts of iron sulfate, sodium dihydrogen phosphate, and disodium hydrogen pyrophosphate were weighed. The sodium dihydrogen phosphate and disodium hydrogen pyrophosphate were added to deionized water to prepare a PO4 3- solution with a concentration of 0.50 mol / L and a P2O7 4- solution with a concentration of 0.22 mol / L. The iron sulfate was added to deionized water to prepare a Fe 3+ solution with a concentration of 0.25 mol / L. An appropriate amount of sulfuric acid was added to adjust the pH to 3.5.

[0067] (2) Solution B was added to the reaction kettle, and argon gas was continuously introduced as a protective gas. Solution A was continuously introduced into the reaction kettle at a flow rate of 1.0 L / h.

[0068] (3) After the reaction is completed, centrifugal drying is performed to obtain a precipitate precursor, and the above raw materials are weighed according to a mass ratio of the precipitate precursor to sodium carbonate, citric acid, and glucose of 37.31:14.01:14.45:1, added to deionized water, stirred into a gel at 50°C, and dried in an oven at 120°C for 48h to obtain an amorphous powder. The above powder is loaded into a crucible, sintered in a box furnace under nitrogen protection, the temperature is raised at a rate of 2°C / min, the first stage is 350°C for 8h, and the second stage is 560°C for 10h; after grinding, a 300-mesh sieve is passed to obtain a non-coated and non-doped sodium iron pyrophosphate positive electrode material.

[0069] Comparative Example 2

[0070] The present comparative example provides a modified sodium iron pyrophosphate positive electrode material and a preparation method thereof, the modified sodium iron pyrophosphate positive electrode material is Na4Fe 1.5 Mn 1.5 (PO4)2P2O7, the preparation method uses a sol-gel method, and specifically includes the following steps:

[0071] Sodium carbonate, iron nitrate, manganese nitrate, and ammonium dihydrogen phosphate are calculated and weighed according to the molar ratio of elements Na:Fe:Mn:P=4:1.5:1.5:4; the above substances are added together into deionized water to mix and prepare a solution with a concentration of 3mol / L of the sum of Fe and Mn ions, and citric acid is added in an equal molar amount of the sum of Fe and Mn elements; heating and stirring at 50°C until the solution becomes gelatinous, drying in an oven at 120°C for 48h to obtain an amorphous powder. The above powder is loaded into a crucible, sintered in a box furnace under nitrogen protection, the temperature is raised at a rate of 2°C / min, the first stage is 350°C for 8h, and the second stage is 560°C for 10h; after grinding, a 300-mesh sieve is passed to obtain the modified sodium iron pyrophosphate positive electrode material.

[0072] Performance Test 1

[0073] 1. The modified sodium iron pyrophosphate positive electrode material prepared in the example is subjected to XRD test.

[0074] The XRD pattern of the modified sodium iron pyrophosphate positive electrode material prepared in Example 1 is shown in Figure 1 .

[0075] 2. The positive electrode materials prepared in the examples and comparative examples are respectively subjected to compaction density test by using a powder compaction density instrument, and the test method is as follows:

[0076] 1-2g of the positive electrode material powder is taken and loaded into the powder compaction density instrument, the minimum pressurization pressure is set to 80MPa, the minimum pressure relief pressure is set to 3MPa, and the pressure holding time is set to 10s, so that the compaction density can be measured.

[0077] The test results are shown in Table 1.

[0078] Table 1

[0079] Group Compacted density (g / cm 3 )]]> Example 1 2.30 Example 2 2.27 Example 3 2.19 Comparative Example 1 1.91 Comparative Example 2 2.12

[0080] As can be seen from the results in Table 1, the compaction density of the product can be effectively improved by using the co-precipitation method provided by the present application to prepare the modified sodium iron phosphate positive electrode material.

[0081] Performance test 2

[0082] 1. The positive electrode materials prepared in the examples and the comparative example were respectively used as positive electrode active materials to assemble button cells:

[0083] The positive electrode materials prepared in the examples and the comparative example were respectively used as positive electrode active materials, and conductive acetylene black (AB) and a binder (4 wt.% polyvinylidene fluoride (PVDF)) were dispersed in N-methyl pyrrolidone (NMP) in a mass ratio of 8:1:1 to prepare a positive electrode slurry. The slurry was homogenized by a vibration homogenizer for at least 15 min, and then uniformly coated on an aluminum foil by using a 150 μm doctor blade. The coated aluminum foil was dried in a vacuum oven at 100 °C for 10 h until the NMP and residual moisture were completely volatilized to obtain a positive electrode sheet. The loading amount of the positive electrode active material was about 2.5 mg / cm 2 .

[0084] In an argon atmosphere glove box (H2O / O2<0.01 ppm), the above positive electrode sheet, sodium sheet, glass fiber membrane and electrolyte (1 mol / L NaClO4 in propylene carbonate solution with 5 vol% fluoroethylene carbonate) were respectively used as a reference electrode, a counter electrode, a separator and an electrolyte to make a button cell.

[0085] 2. Constant current charge-discharge experiments at different rates were carried out on a battery test system. The nominal specific capacity was 129 mAh / g, the voltage window was 1.8-4.2 V, and the charge-discharge rate was carried out in the order of 0.1C, 0.2C, 0.5C, 1C, 5C, 10C, 20C, 30C, 40C and 50C, and each rate was cycled for 5 cycles.

[0086] The test results are shown in Table 2 and Figures 2-4 , wherein, Figure 2 is the first cycle charge-discharge curve of the button cell assembled by the positive electrode material prepared in Example 1-3 and Comparative Example 1 at 0.1C, Figure 3 is the rate performance graph of the button cell assembled by the positive electrode material prepared in Example 1-3 and Comparative Example 1, Figure 4 is the long cycle performance graph of the button cell assembled by the positive electrode material prepared in Example 1-3 and Comparative Example 1 at 1C.

[0087] The results of Table 2 are shown as follows:

[0088] Table 2

[0089]

[0090] It can be found from Table 2 and Figures 2-4 It can be found that the energy density of the sodium ion half-battery assembled by using the modified sodium iron phosphate positive electrode material prepared by the application is significantly improved, and has a high discharge platform voltage, excellent rate performance and cycle performance.

[0091] It can be found from the comparison of Example 1 and Comparative Example 1 that the discharge platform voltage and energy density of the half-battery assembled by the Comparative Example 1 without manganese doping are both low, and the rate performance and cycle performance are poor; it can be found from the comparison of Example 1 and Comparative Example 2 that the energy density of the Comparative Example 2 prepared by the sol-gel method is relatively low, and the rate performance and cycle performance are poor.

[0092] It should be noted that, in this document, relational terms such as“first” and“second”, and the like, are used solely to distinguish one entity or action from another entity or action, without necessarily requiring or implying any actual such relationship or order between such entities or actions. Moreover, the terms“comprises”,“comprising”, or any other variation thereof, are intended to cover a non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements does not include only those elements but can include other elements not expressly listed or inherent to such process, method, article, or apparatus. An element proceeded by“comprises a...” does not, without more constraints, exclude the existence of additional identical elements in the process, method, article, or apparatus that comprises the element.

[0093] The above description is merely that of specific embodiments of the application, making it possible for those skilled in the art to understand or implement the application. Numerous modifications to these embodiments, which are within the purview of those skilled in the art, will be readily apparent to those skilled in the art and the generic principles defined herein can be applied to other embodiments without departing from the spirit or scope of the application. Accordingly, the application is not intended to be limited to the embodiments described herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a modified sodium iron phosphate pyrophosphate cathode material, characterized in that, The preparation method comprises the following steps: (1) reacting an oxalic acid source and an iron source and a manganese source in an aqueous solution to obtain an iron-manganese oxalate intermediate; (2) mixing the iron-manganese oxalate intermediate with a sodium phosphate, a sodium pyrophosphate and a reducing agent, and then heating to obtain a gel-like solid, drying and sintering to obtain the modified sodium pyrophosphate iron phosphate positive electrode material.

2. The production method according to claim 1, characterized by, The step (1) is: continuously adding the oxalic acid source into the aqueous solution of the iron source and the manganese source to react; Preferably, the reaction in step (1) is carried out under the protection of an inert gas atmosphere; Preferably, the pH during the reaction in step (1) is 3.3-3.7; Preferably, the pH is adjusted by a pH adjuster selected from any one or more of sulfuric acid, nitric acid and hydrochloric acid.

3. The production method according to claim 1 or 2, characterized by, The molar ratio of iron in the iron source to manganese in the manganese source is (1.4-2.9):(0.1-1.5); And / or, the ratio of the total molar amount of iron in the iron source and manganese in the manganese source to the molar amount of oxalate ions in the oxalic acid source is 1:(1-1.1).

4. The production method according to any one of claims 1 to 3, characterized by, The oxalic acid source is selected from any one or more of oxalic acid, ammonium oxalate and sodium oxalate; And / or, the iron source is selected from any one or more of ferrous sulfate, ferrous nitrate and ferrous chloride; And / or, the manganese source is selected from any one or more of manganese sulfate, manganese nitrate and manganese chloride.

5. The method of any one of claims 1-4, wherein, The molar ratio of the iron-manganese oxalate intermediate to the sodium phosphate, the sodium pyrophosphate and the reducing agent is 1:2:1:(1.5-6); And / or, the sodium phosphate is selected from any one or more of trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and ammonium hydrogen phosphate sodium; And / or, the sodium pyrophosphate is selected from sodium pyrophosphate and / or disodium pyrophosphate; And / or, the reducing agent is selected from any one or more of citric acid, oxalic acid, sucrose and ascorbic acid.

6. The method of any one of claims 1-5, wherein, The heating temperature is 50-80℃; And / or, the drying temperature is 110-125℃, and the drying time is 18-36h; And / or, the sintering is carried out under the protection of an inert gas atmosphere; And / or, the sintering method is calcination at 350℃ for 3-8h, followed by calcination at 550-650℃ for 8-18h, and the heating rate is 2-5℃ / min.

7. The modified sodium pyrophosphate iron phosphate positive electrode material prepared by the preparation method of any one of claims 1-6.

8. The modified sodium iron phosphate pyrophosphate cathode material of claim 7, wherein, The modified sodium iron pyrophosphate positive electrode material is Na x Fe y Mn z (PO4)2P2O7, Wherein, 4≤x≤4.18, 2.9≤y+z≤3, 0.1<z≤1.5, x+2y+2z=10.

9. A positive electrode sheet characterized by comprising: The positive electrode tab comprises the modified sodium pyrophosphate iron phosphate positive electrode material of claim 7 or 8.

10. A sodium-ion battery, characterized in that, The sodium ion battery comprises the positive electrode tab of claim 9.

Citation Information

Patent Citations

  • Positive electrode material for sodium-ion battery and preparation method thereof

    CN108046231A

  • Preparation method of sodium ferromanganese phosphate-pyrophosphate positive electrode material

    CN119569014A

  • Sodium ferric pyrophosphate material with sodium storage dominant crystal face regulated and controlled by cation doping as well as preparation method and application of sodium ferric pyrophosphate material

    CN120157102A

  • Positive electrode active material and preparation method therefor, and positive electrode sheet, battery cell, battery, and electric device comprising same

    WO2025145712A1